2012
DOI: 10.4103/0975-3583.102705
|View full text |Cite
|
Sign up to set email alerts
|

QT Interval prolongation and dispersion: Epidemiology and clinical correlates in subjects with newly diagnosed systemic hypertension in Nigeria

Abstract: Background:The use of easily obtainable clinical and laboratory parameters to identify hypertensive patients with increased cardiovascular risk in resource limited settings cannot be overemphasized. Prolongation of QT intervals and increased dispersion has been associated with increased risk of cardiovascular death. The study aimed at describing the epidemiology of QT interval abnormalities among newly diagnosed hypertensive subjects and associated clinical correlates.Materials and Methods:One hundred and fort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
34
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 31 publications
6
34
0
Order By: Relevance
“…The mean age of the cases and controls in this study is 62.5 ± 14.3 years and 60.7 ± 13.0 respectively. This is in tandem with the findings by Akintunde et al25 and Mene-Afejuku et al 26 who have reported a higher mean age of 62.1 ± 14.2 years and 64.56 ± 11.85 years respectively among patients with hypertensive heart failure. However, Ogah et al 5 in the Abeokuta HF registry and Ojji et al 2 in Abuja have reported a mean age of 56.6 ± 15.3 years and 54.8 ± 13.2 years respectively.…”
supporting
confidence: 90%
“…The mean age of the cases and controls in this study is 62.5 ± 14.3 years and 60.7 ± 13.0 respectively. This is in tandem with the findings by Akintunde et al25 and Mene-Afejuku et al 26 who have reported a higher mean age of 62.1 ± 14.2 years and 64.56 ± 11.85 years respectively among patients with hypertensive heart failure. However, Ogah et al 5 in the Abeokuta HF registry and Ojji et al 2 in Abuja have reported a mean age of 56.6 ± 15.3 years and 54.8 ± 13.2 years respectively.…”
supporting
confidence: 90%
“…[1718] Due to asymptomatic nature, raised blood pressure remains unnoticed and without correction of the same repolarization abnormality can flare owing to LVH. Despite 33% prevalence of hypertension in urban India, only 42% are treated for the same,[2] and the majority of undiagnosed, like the newly diagnosed cases of our study group, forming submerged part of the iceberg, is left at risk of abnormal outcomes of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…The QT interval is a measure of the duration of ventricular depolarization and repolarization, and is a method of screening for those at increased risk of cardiac arrhythmias (21). QTc prolongation is also associated with various components of the insulin resistance syndrome, age, body mass index, left ventricular hypertrophy and resistant hypertension (22). A significant proportion of study participants also had QTc prolongation and this was more frequent among women than men.…”
Section: Discussionmentioning
confidence: 99%